Revealing The Local Wisdom of Madura in the Folk Songs Pajjhâr Lagghu and Tondu' Majhâng: An Ethnolinguistic Study - SANTUSO, Santuso; SETIAWAN, Ikwan; BADRUDIN, Ali (Journal of Social Sciences and Cultural Study, 2024)
Folk songs are not merely a form of entertainment but also serve as a medium to understand the local wisdom embedded within a community. This study aims to uncover the local wisdom of Madura through the folk songs Pajjhâr Lagghu and Tondu' Majhâng. The research employs a qualitative descriptive method with an ethnolinguistic approach. The data consists of words, phrases, and clauses found in the two songs. Data sources include internet sites, YouTube, and textbooks. Data collection was conducted by downloading song videos from YouTube and reviewing song lyrics from websites and books. The collected data were analyzed using an extra lingual matching method. The findings reveal that the local wisdom in Pajjhâr Lagghu encompasses (a) values such as hope, high optimism, hard work, perseverance, resilience, independence, fighting spirit, courage, responsibility, dedication, and strong commitment; (b) knowledge and skills in agrarian enterprises; and (c) patriotism, including the willingness to sacrifice everything for the prosperity and glory of the homeland. Meanwhile, the local wisdom in Tondu' Majhâng includes (a) values such as courage, resilience, perseverance, hard work, togetherness, solidarity, hope, supportiveness, gratitude, and a strong work ethic; and (b) knowledge and skills related to maritime sciences.